BAGAIMANA MENGEMBANGKAN PARA MANAJER MELALUI METODE INFORMAL - Muhammad Gandhi (Universitas Trisakti, 2001)
It seems that the informal training may have a better result than does on training program. Formal training is a well plan program. The paper argues that informal program is ideally a compliment informal of a formal training. Besides formal training, there should be an informal program which will acquaint them with a more specific jab or assignment and which undertakes their quality of expertise of individuals.